Assessment and teaching of 21st century skills methods and approach - Griffin, Patrick; Care, Esther (London Springer, 2015)
"This second volume of papers from the ATC21STM project deals with the development of an assessment and teaching system of 21st century skills. Readers are guided through a detailed description of the methods used in this process. The first volume was published by Springer in 2012 (Griffin, P., McGaw, B. & Care, E., Eds., Assessment and Teaching of 21st Century Skills, Dordrecht: Springer). The major elements of this new volume are the identification and description of two 21st century skills that are amenable to teaching and learning: collaborative problem solving, and learning in digital networks. Features of the skills that need to be mirrored in their assessment are identified so that they can be reflected in assessment tasks. The tasks are formulated so that reporting of student performance can guide implementation in the classroom for use in teaching and learning. How simple tasks can act as platforms for development of 21st century skills is demonstrated, with the concurrent technical infrastructure required for its support. How countries with different languages and cultures participated and contributed to the development process is described. The psychometric qualities of the online tasks developed are reported, in the context of the robustness of the automated scoring processes. Finally, technical and educational issues to be resolved in global projects of this nature are outlined." -- from the publisher.
Part I Project Method and Overview -- Chapter 1 The ATC21S Method -- Part II Conceptual Framework for Internet Based Collaborative Assessment Tasks -- Chapter 2 A Framework for Teachable Collaborative Problem Solving Skills -- Chapter 3 Assessment of Learning in Digital Networks -- Part III Delivery of Collaborative Tasks, Their Scoring, Calibration and Interpretation -- Chapter 4 Collaborative Problem Solving Tasks -- Chapter 5 Platforms for Delivery of Collaborative Tasks -- Chapter 6 Automatic Coding Procedures for Collaborative Problem Solving -- Chapter 7 Tasks Characteristics and Calibration -- Chapter 8 Australia in the Context of the ATC21S Project -- Chapter 9 Student and Teacher Responses to Collaborative Problem Solving and Learning Through Digital Networks in Singapore -- Chapter 10 Introducing Assessment Tools for 21st Century Skills in Finland -- Chapter 11 Case Study on the Implementation of ATC21S in the United States -- Chapter 12 The Adaptation and Contextualization of ATC21S by Costa Rica -- Chapter 13 ATC21S Trials of Collaborative Problem Solving Tasks in the Netherlands -- Part V Implementation at Classroom and System Leveks -- Chapter 14 Linking Developmental Progressions to Teaching -- Chapter 15 Policy Pathways for Twenty-First Century Skills.
Includes references.
Keywords: Educational evaluation; Educational assessment; 21st century skills